Psychopedagogical intervention strategies for shyness in adolescents - Barrionuevo Alvarado, Karem Kadeesi; Vigoa Escobedo, Yisell (International Journal of Neurology, 2025)
Introduction: adolescence constitutes a critical stage of human development, characterized by profound biological, psychological, and social transformations. Objective: to characterize aspects related to pedagogical interventions for adolescents with shyness. Methods: a bibliographic review was conducted in the PubMed, Scopus, Web of Science, and Google Scholar databases for the period 2018–2024. Original studies, reviews, and meta-analyses in Spanish and English were included. A total of 14 reference articles were used. Results: shyness is identified as a multifactorial phenomenon, influenced by biological, familial, pedagogical, and social components. The most effective interventions are those of a comprehensive nature, which combine the development of social skills (role-playing, assertive communication), the strengthening of self-esteem and self-efficacy, and the creation of a safe and inclusive school environment. Strategies such as cooperative learning, group dynamics, and family involvement are crucial for reducing social anxiety and encouraging active participation. Conclusion: psychopedagogical intervention strategies for adolescent shyness should be systemic and multimodal, simultaneously addressing the emotional, social, and cognitive dimensions.